Description of the mitochondrial genome of the tree coral Dendrophyllia arbuscula (Anthozoa, Scleractinia) - Luz, Bruna Louise Pereira; Capel, Kátia Cristina Cruz; Stampar, Sérgio Nascimento [UNESP]; Kitahara, Marcelo Visentini (My University, 2015)
Dendrophylliidae is one of the few monophyletic families within the Scleractinia that embraces zooxanthellate and azooxanthellate species represented by both solitary and colonial forms. Among the exclusively azooxanthellate genera, Dendrophyllia is reported worldwide from 1 to 1200 m deep. To date, although three complete mitochondrial (mt) genomes from representatives of the family are available, only that from Turbinaria peltata has been formally published. Here we describe the complete nucleotide sequence of the mt genome from Dendrophyllia arbuscula that is 19 069 bp in length and comprises two rDNAs, two tRNAs, and 13 protein-coding genes arranged in the canonical scleractinian mt gene order. No genes overlap, resulting in the presence of 18 intergenic spacers and one of the longest scleractinian mt genome sequenced to date.
Keywords: Dendrophyllia arbuscula; Mitochondrial genome; Scleractinia; DNA Mitocondrial; Cnidaria; Biologia Marinha; Biologia Molecular